Analisis Kepuasan Pengguna Feri Penyeberangan Mintin Kabupaten Pulang Pisau - Pratama, Ramadani; Elvina, Ina; Supiyan, Supiyan (Jurnal Talenta Sipil, 2024)
As a form of public transportation, the operation of ferry services often attracts public attention. One of them is the public's complaint about the operation of the Mintin crossing line where the service system takes a long time, causing passengers to queue at the port or wait a long time on the crossing ferry. This study aims to analyze the satisfaction of users of the Mintin ferry crossing in Pulang Pisau Regency. The method used is Importance Perfomance Analysis (IPA) In the reliability variable, the performance dimension of the respondent answered 58.46% quite satisfied and in the importance dimension 84.40% stated very important. The assurance dimension, the performance respondent answered 64.25% satisfied and the importance dimension 91.10% stated that it was very important. The empathy dimension, the performance dimension, the respondents answered 68.70% satisfied and at the importance dimension 89.60% stated that it was very important. The dimension of responsiveness, at 58.60% performance is quite satisfied and at 87.00% importance states very important. In the tangible variable, the respondent's performance dimension answered 56.60% quite satisfied and at 83.84% importance stated very important.